South Caucasus and Central Asia - The Belt and Road Initiative : Tajikistan Country Case Study - World Bank (World Bank, Washington, DC, 2020)
Tajikistan is the poorest country in the region despite strong growth for nearly two decades; sustaining growth in future will need substantially higher growth in private investment and exports. Its per capita income (GNI) is close to US$1,000 but nearly a third of its population, of around 9 million, live in poverty. Its growth of 6-7 percent per year since 2000 was fueled by growth in consumption and public investment, the latter driven mainly by rising remittances and export receipts from aluminum and cotton. Private investment and growth of other exports remained weak, and the fiscal situation, fragile for most of that period. Accordingly, the National Development Strategy 2030 (NDS) seeks to address those weaknesses. This note attempts to highlight the potential economic impact of BRI on the Tajik economy. It looks at how, if fully implemented globally, the BRI is expected to achieve better transport connections and greater economic integration of participating BRI countries, discusses improvements in Tajikistan’s cross-border transport, electricity and ICT infrastructure to-date, and assesses the potential impact of the completion of all BRI transport projects on Tajik shipment time. It further looks at the likely economic impact of BRI reductions in shipment time on exports, FDI and GDP, and the spatial distribution of benefits within the country and at how complementary polices can enhance the positive impact and mitigate risks. Finally, it examines the fiscal risk of Tajikistan’s scaling-up of investment in BRI transport projects in the coming years without undermining medium-term debt sustainability.